Adaptation of the Questionnaire Parental Mediation Of Children's Media Activity by G. Nimrod, D. Lemish, N. Elias on a Russian Sample of Parents of Older Preschoolers - N.S. Denisenkova; P.I. Taruntaev; V.V. Fyodorov (Психолого-педагогические исследования)
The issue of digitization of modern childhood is attracting increasing attention from researchers. In most cases, we obtain information about how preschoolers use various gadgets from parents. Literature analysis has shown that many authors consider the strategies through which adults regulate and mediate the influence of digital devices and various media products on children as the most adequate parameter for studying parental mediation of children's media activity. However, there are not many tools available for studying this phenomenon. Such questionnaires are more common in English-language literature. The task was to adapt the questionnaire "Parental Mediation of Children's Media Activity" by G. Nimrod, D. Lemish, and N. Elias, which has proven itself well, for the Russian-speaking sample. The study involved 322 parents of children in the upper preschool age group attending kindergartens in large and small cities (average age of parents was 28.5 years, including 237 women and 85 men). The study showed that the adapted Russian-language questionnaire differs from the original in its factor structure and consists of 12 statements and three scales: restrictive mediation strategy, instructive mediation strategy, and co-use. The Russian-language questionnaire demonstrates test-retest reliability, internal consistency, construct, and convergent validity, and can be used to study parental mediation and assess children's media activity for the Russian-speaking sample.